Italian-American selfhood in the realm of cultural inbetweenness portrayed in "Sometimes I Dream in Italian" by Nina Ciresi - Mobley, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the novel "Sometimes I Dream in Italian", Nina Ciresi envisions the complexity of Italian American selfhood through the reconstruction of the experiences of post-WW II Italian immigrants in the United States and of the generation that followed. The account of the character-narrator, Angel Lupo, a woman in her thirties, constitutes a patchwork of storylines that present primarily her plight as well as that of her parents and of her elder sister, Lina.
Keywords: Italian-Americans; inbetweenness; American Dream; heritage; identity